Perspectives on the Islamic Economic and Financial System in the Contemporary World - Azharsyah Ibrahim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
The majority of submissions for this issue focused on the challenges faced by IBFIs as a result of the global spread of Covid-19. They discuss the trends in Islamic economics research, the importance of Islamic economics and finance to the modern economy, the performance of institutions and their employees, financial stability, waqf institutions, and the role of Islamic economics and finance in society. Only 12 of the dozen papers submitted for consideration were eventually chosen for publication. As usual, each manuscript will have to pass an initial review from our editor(s) before forwarding it to suitable reviewers. Some manuscripts would have to go through several rounds before being accepted. The reviewers' feedback was taken into consideration to provide the final decisions. Following that, the manuscripts would have to pass the editing stages, including proofreading and layout, where our editor(s) will intensely communicate with the authors if needed. It is to ensure that each published manuscript has undergone a quality check.